Diagnostic accuracy of intracellular uptake rates calculated using dynamic Gd‐EOB‐DTPA‐enhanced MRI for hepatic fibrosis stage. Issue 4 (16th August 2016) - Juluru, Krishna; Talal, Andrew H.; Yantiss, Rhonda K.; Spincemaille, Pascal; Weidman, Elizabeth K.; Giambrone, Ashley E.; Jalili, Sadaf; Sourbron, Steven P.; Dyke, Jonathan P.
Abstract : Purpose: To assess the diagnostic accuracy of intracellular uptake rates ( K i ), and other quantitative pharmacokinetic (PK) parameters, for hepatic fibrosis stage; to compare this accuracy with a previously published semiquantitative metric, contrast enhancement index (CEI); and to assess variability of these parameters between liver regions. Materials and Methods: This was a case–control study design. Dynamic Gd‐EOB‐DTPA‐enhanced 1.5T magnetic resonance imaging (MRI) was performed prospectively in 22 subjects with varying known stages of hepatic fibrosis. PK parameters and CEI were derived from the whole livers and from three fixed regions of interest (ROIs) in all subjects. Spearman rank correlation coefficients were computed to assess the relationship between fibrosis stages and each parameter. Receiver operating characteristic (ROC) curves were constructed to discriminate severe fibrosis (stages 3–4) from nonsevere fibrosis (stages 0–2). The coefficient of variation (CV) was calculated to assess variability in parameters between ROIs. Results: K i and fibrosis stage were significantly correlated (R = –0.55, 95% confidence interval [CI] [–0.79, –0.14], P  = 0.01). Area under ROC curve (AUC) in distinguishing severe from nonsevere fibrosis for K i was 0.84 (95% CI [0.65, 1.00]), and for CEI was 0.64 (95% CI [0.39, 0.89]) ( P  = 0.0248). CV for K i and CEI were 33.4 and 5.8, respectively. The only other parameter in the PK model having significant correlation with fibrosis stage was absolute arterial blood flow ( F a ) (R = –0.48, 95% CI [−0.75, −0.05], P  = 0.03). Conclusion: Hepatocyte intracellular uptake rate, Ki, derived from dynamic contrast‐enhanced MRI, correlates with fibrosis stage and may contribute to a noninvasive biomarker of hepatic fibrosis. Level of Evidence: 2 J. Magn. Reson. Imaging 2017;45:1177–1185